2006
DOI: 10.1186/1746-4269-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Gitksan medicinal plants-cultural choice and efficacy

Abstract: Background: The use of plants for healing by any cultural group is integrally related to local concepts of the nature of disease, the nature of plants, and the world view of the culture. The physical and chemical properties of the plants themselves also bear on their selection by people for medicines, as does the array of plants available for people to choose from. I examine use of medicinal plants from a "biobehavioral" perspective to illuminate cultural selection of plants used for medicine by the Gitksan of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…The selection of medicinal plants can be influenced by various kinds of factors that act synergistically, such as socio-cultural (Johnson, 2006), ecological/environmental (Almeida et al, 2005;Albuquerque, 2010), epidemiological and cognitive (Berlin and Berlin, 2005), among others. Thus, a given society's body of knowledge about medicinal plants reflects the particular environment (see reviews by Agra et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of medicinal plants can be influenced by various kinds of factors that act synergistically, such as socio-cultural (Johnson, 2006), ecological/environmental (Almeida et al, 2005;Albuquerque, 2010), epidemiological and cognitive (Berlin and Berlin, 2005), among others. Thus, a given society's body of knowledge about medicinal plants reflects the particular environment (see reviews by Agra et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported a different scenario on this issue, which illnesses are often attributed to supernatural causes. For example, the meaning of illness to the Gitksan in British Columbia, Canada, is often attributed to spiritual factors (Johnson, 2006). Hurrell (1991) reported that respondents in Iruya and Santa Victoria, in Argentina, indicated that illnesses are the result of a change in the relationship between humans and the environment (surroundings), with spiritual and non-spiritual origins, or diseases that manifest in themselves in the body and in the spirit.…”
mentioning
confidence: 98%
“…The major effects of this plant are similar to those of well-known botanicals of the same family such as American ginseng ( Panax quinquefolius ) and Asian ginseng ( P. ginseng ) (Lin et al, 2008; Schofield, 2000; Wang et al, 2007). The root bark and berries of O. horridus have been used for treating a variety of ailments including arthritis, cold and fever, infections, diabetes, respiratory and gastrointestinal disorders, and cancer (Johnson, 2006; Moore, 1993; Schofield, 2000). Chemical investigations into O. horridus revealed that this plant consists of two major groups of constituents.…”
Section: Introductionmentioning
confidence: 99%
“…One species, O. horridus, is even regarded to be on par with Oriental ginseng and is used as a body-balancing and system-strengthening tea (Schofield, 2000). In traditional medicinal use, the stem and root of O. elatus is used for treating neurasthenic, hypopiesis, schizophrenia, cardiovascular diseases, diabetes mellitus and rheumatism ( Academy of Traditional Chinese Medicine and Traditional Chinese Herb of Ji-lin Province, 1982); the root, bark and stem of O. japonicus are used as an antipyretic or cough medicine (Takeda et al , 1966); the bark or berries of O. horridus are often used in the form of an extract for the treatment of arthritis (inflammation), hyperglycemia, gastrointestinal disorders, infections and respiratory ailments (Johnson, 2006; Moore, 1993; Schofield, 2000). It is believed that the dammarane-type triterpenoids are related to the bioactivities of ginseng (Kang et al , 2008; Zuo et al , 2009).…”
Section: Introductionmentioning
confidence: 99%